Analisis Keterampilan Komunikasi Mahasiswa Pendidikan Biologi UIN Alauddin Makassar berdasarkan Gender - Ali, Ahmad; Irhas, Muhammad (Al Asma: Journal of Islamic Education, 2025)
Communication skills are one of the important competencies of the 21st century that students need to master. This study aims to describe the communication skills of students in the Biology Education Study Program at UIN Alauddin Makassar and analyze the differences in terms of gender. This study uses a quantitative descriptive method. The study population was 138 odd semester students of the 2024/2025 Academic Year (118 females and 20 males). The sample was selected using an accidental sampling technique, resulting in 97 students (12 males and 85 females). Data were collected through self-assessment and peer-assessment questionnaires with a Likert scale of 1-4. Data analysis used descriptive statistics (percentage) and inferential statistics (t-test). The results showed that the average communication skills score of male students was 2.99, while that of females was 3.16. The results of the t-test (two-tailed) showed a p-value of 0.194 (p > 0.05). This indicates that there is no statistically significant difference in communication skills between male and female students.